Photophysical properties of donor (D)-acceptor (A)-donor (D) diketopyrrolopyrrole (A) systems as donors for applications to organic electronic devices - Rosa, Nathália M P (Journal of computational chemistry, 2024)
© 2024 Wiley Periodicals LLC.